2019
DOI: 10.1002/aenm.201902799
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Mechanistic Elucidation of Superior Si‐C‐Graphite Li‐Ion Battery Anode Formation with Thermal Safety Aspects

Abstract: understanding of the material synthesis/ fabrication, interfacial behavior, and thermal-chemical stabilities are vital. [3] With electronic appliances requiring stable voltage delivery, the current LIBs employ graphite or mixtures with soft carbons (carbon black) to achieve stable performance at discharge curves. [4] Since 1991, various forms of ordered and disordered (i.e., soft and hard) carbon have been primarily used as anode materials. [5] With graphitic carbon, a compromise was identified, which delivere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 57 publications
3
49
0
Order By: Relevance
“…It delivered stable discharge-charge capacities of 628/600 mAh g −1 for 3rd cycle (Figure 4b). The yielded capacities of C-Si material were almost closer to the Li versus C-Si half-cell results discharge-charge capacities of 641/627 mAh g −1 (40th cycle) at 0.1 C between 0.01and 2.0 V, [26,45] as shown in Figure S13 in the Supporting Information and higher than the Li versus MCMB half-cell results, discharge-charge capacities 390/388 mAh g −1 (75th cycle) at 0.1 C between 0.01 and 1.5 V as shown in Figure S7 in the Supporting Information, for the reason of Si contribution during alloying and dealloying reaction.…”
Section: Direct In Situ Sei Formation On C-si Anode For Lithium-ion Fsupporting
confidence: 66%
See 2 more Smart Citations
“…It delivered stable discharge-charge capacities of 628/600 mAh g −1 for 3rd cycle (Figure 4b). The yielded capacities of C-Si material were almost closer to the Li versus C-Si half-cell results discharge-charge capacities of 641/627 mAh g −1 (40th cycle) at 0.1 C between 0.01and 2.0 V, [26,45] as shown in Figure S13 in the Supporting Information and higher than the Li versus MCMB half-cell results, discharge-charge capacities 390/388 mAh g −1 (75th cycle) at 0.1 C between 0.01 and 1.5 V as shown in Figure S7 in the Supporting Information, for the reason of Si contribution during alloying and dealloying reaction.…”
Section: Direct In Situ Sei Formation On C-si Anode For Lithium-ion Fsupporting
confidence: 66%
“…All the diffraction peaks of MCMB and LiFePO 4 are well indexed with standard patterns JCPDS# 00‐008‐0415 (indicated in red for MCMB) [ 44 ] and JCPDS# 00‐040‐1499 (indicated in pink for LiFePO 4 ), [ 17 ] and confirmed that no other impurity phase was present (Figure 1f). Similarly, the C–Si anode (purple) and LiNi 1/3 Mn 1/3 Co 1/3 O 2 cathode (brown) materials were compared with the standard XRD patterns of C, JCPDS# 00‐008‐0415 (orange) [ 32,45 ] and Si, JCPDS# 01‐089‐2749 (cyan) [ 32,45 ] and LiNi 1/3 Mn 1/3 Co 1/3 O 2 , JCPDS# 01‐087‐1564 (violet) [ 28,46 ] as shown in Figure 1g. All the inset FESEM images are associated with the respective electrode material morphology, given in Figure S1 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon originated from wheat flour delivered a good specific capacity of 390 mAh g −1 at 1C with a good rate and cycle performance for LIBs [ 28 ]. The wheat flour-based carbon materials have been used as various kinds of electrode materials for supercapacitors and other batteries recently [ 27 , 29 , 30 , 31 , 32 ]. Recently, metal and metallic oxide encapsulated into porous carbon is considered to be a simple method to obtain composite with good electrochemical property, such as Sb/C composite [ 33 ], MnO/metal/carbon nanohybrid [ 34 ], CuO/C [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…To solve these issues, the major focus has been on material engineering by nanotechnology. Through morphology control and nanostructuring, many novel active materials have showed promising electrochemical performance in a laboratory cell [6][7][8][9][10]. However, nanotechnology that is cost-effective and can be used on an industrial scale is still lacking.…”
mentioning
confidence: 99%